Medit͡sina v Kuzbasse - Kemerovskai͡a gosudarstvennai͡a medit͡sinskai͡a akademii͡a; Russia (Federation). Ministerstvo zdravookhranenii͡a; Kemerovskai͡a oblastʹ (Russia). Departament okhrany zdorovʹi͡a naselenii͡a (NP "Gorodskoĭ Medit͡sinskiĭ Klub", 2002)
"Ret͡senziruemyĭ nauchno-prakticheskiĭ medit͡sinskiĭ zhurnal."
Keywords: Medicine : Periodicals; Public health : Periodicals; Public health; Medicine